LEVERAGING REAL-WORLD DATA IN PHARMACEUTICAL INFORMATION TECHNOLOGY: ADVANCING DRUG DEVELOPMENT AND PATIENT CARE - Srinivas Maddela, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
Integrating Real-World Data (RWD) with pharmaceutical information technology has fundamentally transformed healthcare delivery and drug development processes. This comprehensive article examines how RWD from electronic health records, insurance claims, and patient registries has revolutionized clinical decision-making, regulatory compliance, and patient care outcomes. Implementing RWD has enabled more efficient clinical trial design, enhanced post-market surveillance, and improved therapeutic effectiveness assessment. Healthcare providers have benefited from advanced clinical decision support systems and quality improvement initiatives, while regulatory bodies have strengthened their decision-making processes through enhanced data analysis capabilities. Despite technical challenges in data integration and analytics infrastructure, organizations have developed robust solutions for managing complex healthcare data systems, significantly improving patient care delivery and pharmaceutical research outcomes.